Antifungal activity of Zataria multiflora essential oil-loaded solid lipid nanoparticles in-vitro condition - Mahboobeh Nasseri; Shiva Golmohammadzadeh; Hossein Arouiee; Mahmoud Reza Jaafari; Hossein Neamati (Iranian Journal of Basic Medical Sciences, 2016)
Objective(s): The aim of the present study was to prepare, characterize, and evaluate solid lipid nanoparticles (SLNs) containing Zataria multiflora essential oil (ZEO). Materials and Methods: In this study, Z. multiflora essential oil-loaded solid lipid nanoparticles (ZE-SLNs) were prepared to improve its efficiency in controlling some fungal pathogens. SLNs containing Z. multiflora essential oil were prepared by high shear homogenization and ultra sound technique. ZEO-SLNs contained 0.03% ZEO in 5% of lipid phase (Glyceryl monostearate-GMS and Precirol® ATO 5).Tween 80 and Poloxamer 188 (2.5% w/v) were used as surfactant in the aqueous phase. The antifungal efficacy of ZE-SLNs and ZEO was compared under in vitro conditions. Results:The particle size of ZE-SLNs was around 255.5±3 nm with PDI of 0.369±0.05 and zeta potential was about -37.8±0.8 mV. Encapsulation efficacy of ZE-SLNs in crystalline form was 84±0.92%. The results showed that the ZEO and ZE-SLNs had 54 and 79% inhibition on the growth of fungal pathogens, respectively. The minimum inhibitory concentration (MIC) under in vitro conditions for the ZEO on the fungal pathogens of Aspergillus ochraceus, Aspergillus niger, Aspergillus flavus, Alternaria solani, Rhizoctonia solani, and Rhizopus stolonifer was 300, 200, 300, 200, 200 and 200 ppm, respectively, for ZE-SLNs, it was 200, 200, 200, 100, 50 and 50 ppm. The antifungal efficacy of ZE-SLNs was significantly more than ZEO. Conclusion: Our results showed that the SLNs were suitable carriers for Z. multiflora essential oil in controlling the fungal pathogens and merits further investigation.